2007
DOI: 10.1007/s10654-006-9091-0
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the design of web-based questionnaires – experience from a population-based study among 50,000 women

Abstract: An additional 6% units of completers--persons initiating and completing the questionnaire--can be obtained by considering the ordering of questions. A group uniquely identified in web-surveys, as lurkers are potentially easier to persuade to complete an already started web-questionnaire compared to a non-responder. Lurkers thus constitute a unique opportunity of decreasing the drop out rate and therefore merit future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 15 publications
4
35
0
Order By: Relevance
“…The proportion of partial respondents in our study was small and similar to that observed in the web-based health survey of 47,859 Swedish women mentioned above [24]. It has been observed that responses to a web version of a questionnaire are usually more complete than the responses to a printed questionnaire [6].…”
Section: Discussionsupporting
confidence: 80%
“…The proportion of partial respondents in our study was small and similar to that observed in the web-based health survey of 47,859 Swedish women mentioned above [24]. It has been observed that responses to a web version of a questionnaire are usually more complete than the responses to a printed questionnaire [6].…”
Section: Discussionsupporting
confidence: 80%
“…However, this is a constant concern irrespective of method and might not be larger in web-studies. This was shown by Ekman et al, in a population-based cohort study of 50,000 women [26]. Although there were some suggestions of a non-response bias, there was no difference between the web and paper mode used, which has also been confirmed by others [37][38][39].…”
Section: Data Qualitysupporting
confidence: 54%
“…A group uniquely identified in web-surveys are lurkers, participants that enter, start responding to, but do not complete a webquestionnaire. Lurkers are potentially easier to persuade to complete an already started web-questionnaire compared to a non-responder and thus constitute a unique opportunity of decreasing the drop out rate and therefore merit future research [26,27].…”
Section: Response Ratementioning
confidence: 99%
“…New methods for contacting participants, which have been used in other more recently started studies, including use of internet, sms and e-mail, are currently being explored [92, [252][253][254][255][256][257][258][259][260][261][262].…”
Section: Follow Up and Retention Strategiesmentioning
confidence: 99%